From Believing to Doing: The Association Between Leadership Self-Efficacy and the Developmental Leadership Model - Bergman, David; Gustafsson-Sendén, Marie; Berntson, Erik (Frontiers in Psychology, 2021)
the current study examined the association between leadership self-efficacy and the developmental leadership model. The purpose is to better understand how leadership training transfers to facets of developmental leadership. This was tested in a cross-sectional design with military commanders in the Swedish armed forces. The results show that the sub-domain of leader self-control efficacy (the cognitive and emotional ability to remain composure) did predict developmental leadership in only one dimension of being an exemplary model, but that leader assertiveness efficacy (the ability to make rational decisions) predicted the two dimensions of exemplary model and inspiration & motivation in developmental leadership. One possibility is that leader self-control efficacy can be what enables the individual to function within an extreme context, but leader assertiveness efficacy can be what most determine the leadership performance within that context. The possibility for mediatory analyses in further research is discussed.